SELF-ESTEEM IN EMERGING EDUCATORS: AN EVALUATION USING THE KARL PERERA FRAMEWORK (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research paper provides an in-depth analysis of self-esteem levels among teacher trainees, employing the Karl Perera self-esteem test as the primary assessment tool. Self-esteem, defined as an individual's sense of self-worth and confidence, is a fundamental aspect of both personal and professional development. For teacher trainees, who are at a pivotal stage in their career preparation, self-esteem is especially crucial. It impacts their ability to confidently engage with students, manage classroom dynamics, and navigate the challenges of the teaching profession.In the context of education, where teachers play a critical role in shaping the minds and attitudes of young learners, the self-esteem of educators is directly linked to their teaching effectiveness and student outcomes. High levels of self-esteem in teachers contribute to a positive classroom environment, where students are more likely to be motivated, engaged, and successful. Conversely, low self-esteem can hinder a teacher's ability to assert themselves, lead effectively, and inspire confidence in their students.The purpose of this study is to assess and identify the prevailing trends in self-esteem levels among teacher trainees. By examining these trends, the study seeks to uncover underlying factors that contribute to variations in self-esteem within this group. Additionally, the research explores the potential implications of these self-esteem levels on the trainees' future careers as educators.The findings from this study are anticipated to offer valuable insights that can inform the design and implementation of teacher training programs. By understanding the self-esteem profiles of teacher trainees, educators and program developers can devise targeted interventions and support mechanisms to enhance self-esteem. Such interventions may include confidence-building workshops, mentorship programs, and stress management strategies, all aimed at fostering a robust sense of self-worth among trainees.Ultimately, the goal of this research is to contribute to the overall effectiveness of teacher education by ensuring that future teachers enter the profession with the confidence and self-efficacy needed to thrive in their roles. By addressing self-esteem early in their training, teacher education programs can play a pivotal role in developing well-rounded, competent, and resilient educators who are better equipped to meet the demands of the teaching profession.